Lipid Constituents from Cissus quadrangularis Leaves - Jain Vandana; Thakur Achal; Hingorani Lal; Laddha KS (Pharmacognosy Research, 2009)
A phytochemical investigation of Cissus quadrangularis leaves yielded five additional known compounds including eicosyl eicosanoate, tetratriacontanol, tetratriacontanoic acid, α-amyrin and β-sitosterol. The characterization of isolated compounds was achieved by chemical and spectral studies (IR, 1H NMR and Mass Spectroscopy).
Keywords: Cissus quadrangularis; Lipids; Vitaceae